Sensory acceptability of probiotic mango (mangifera indica) yogurt enriched with dehydrated pasteurized egg albumin - Jordan-Suarez, Oscar (2017)
Samples of a probiotic mango (Mangifera indica) yogurt were prepared with three percentages of dehydrated pasteurized egg albumin (1, 2 and 3%), which were assessed by thirty different consumers (by triplicate) in terms of Appearance, Texture and Flavor. Yogurt enriched with 2% of albumin showed the greatest acceptance for Flavor, and a protein content of 5.32 g/100 g; this amount represents an increase of 80% in comparison with the average protein content of five commercial yogurts.The amount of probiotic microorganisms found in the yogurt was 1.5x109 cfu/g, wherein the amount of 18x104 cfu/g were exclusively bifidobacterias.